COVID-19 pandemic and management on hospital length of stay: A review - Fatemeh Abdollahi (PAGEPress Publications, 2021)
COVID-19 virus is a serious threat to public health everywhere on the planet. The World Health Organization (WHO) declared the disease epidemic in December 2019 because of its rapid prevalence around the world. The disease is transferred by inhalation or contact with contaminated droplets, and the incubation period varies from 2 to 14 days. COVID-19 has led to unprecedented pressures as demand for healthcare in hospitals and intensive care units around the world increases. As the epidemic intensifies, determining the resulting needs for health care resources (beds, staff, equipment) has become a priority for many countries. Predicting future demand requires estimating how long COVID-19 patients must have access to different levels of hospital care. The length of hospitalization for these patients is one of the management priorities. It is possible to pass through the crisis only with careful planning and comprehensive cooperation.